Mind the gap: Bridging evidence-based witness identification procedures to practice through police training - Cecconello, William Weber (International journal of police science & management, 2023)
Research has led to evidence-based eyewitness identification procedures, but empirical research on how to train police officers in such techniques is limited. We tested the effectiveness of the FAIR (Find a suspect, Avoiding bias, Instructing the witness, Record the procedure) eyewitness identification training program with 88 Brazilian police officers. The hypothesis that FAIR training would improve identification procedures was supported by pre- and post-training assessment of performance on a lineup construction task. Training increased the likelihood that police officers would construct lineups with known-innocent fillers and provide recommended pre-lineup instructions to witnesses (e.g., stating that the witness is not required to make an identification). Training also decreased non-recommended lineup practices, such as revealing the identity of the main suspect after a witness response. Feedback from the participants supports the conclusion that FAIR training improved knowledge of how to build lineups, instruct witnesses, and avoid undesirable and potentially biasing practices. Nevertheless, participants anticipated that incorporating the reform procedures into practice would provoke resistance from superiors and colleagues, which highlights the need for FAIR training to be supported by infrastructure, resources and policy that enable police officers to use evidence-based procedures in eyewitness identification.